ANALYSIS OF PRODUCTION COST EFFECT WITH ORDER PRICE METHOD ON SALES PRICING OF PRODUCTS AT PT. ANEKA PRINTING INDONESIA IN SUKOHARJO - Maya Widyana Dewi; Muryati Muryati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
This study aims to determine and analyze the calculation of the cost of production of screen printing based on the cost of order method whether it has been in accordance with the theory of cost accounting by comparing the calculation of cost of goods manufactured by the company with the calculation of cost of production based on the cost accounting theory that is using full costing method, As well as to know how much influence the cost of production to the determination of product selling price. This study uses primary data in the form of information obtained from the owner of the company or parties concerned and secondary data with population and sample data of cost of production and selling price of screen printing orders during January 2017. Data collection methods used are literature research methods, interviews and Method of documentation. While the method of data analysis used is by using simple regression analysis, coefficient of determination and hypothesis test using t test by using the tool program SPSS 16.0 for windows. From the results of research indicate that the calculation of cost of production based on the results of analysis using full costing method is greater than the calculation of cost of production method company. This difference occurs because the loading of factory overhead cost calculated using full costing method more thorough and detailed. Based on the tests conducted known that the cost of production has a very strong influence on the sale price. The influence of the cost of production to the selling price in this study is 91%, and the remaining 9% is influenced by other factors (variables) such as demand, supply, and other unreported variables. Keywords:Cost of Production, Selling Price